Quality of education in public schools in Brazil: an analysis of the correlation between investment per student and performance in the national assessments - Moraes, Joysi; Dias, Bruno Francisco Batista; Mariano, Sandra Regina Holanda (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
In this article, we adopted the economic perspective of education. This approach assumes that the quality of education can be measured by the effectiveness of the use of available resources. The correlation between investment per pupil in primary education, from 2005 to 2015 (from the beginning of the historical series to the last evaluation), and the outcome of the students in the evaluation of the Development Index of Basic Education (Ideb) in each state was analyzed. In the analysis per region (North, Northeast, Center-West, Southeast and South), the educational systems that used the available resources in the best manner were those of Roraima, Pernambuco, Goiás, Minas Gerais and Paraná states. Only in the states of Minas Gerais, Pernambuco and Goiás, there was a correlation between the improvement of student learning, as measured by Ideb, and the increase in investment per student.